Early Evaluation Findings From a Federally Funded Training Program: The Public Health Associate Program. Issue 5 (September 2017) - Sobelson, Robyn K.; Young, Andrea C.; Wigington, Corinne J.; Duncan, Heather
Abstract : Objective: The Centers for Disease Control and Prevention (CDC) created the Public Health Associate Program (PHAP) to establish a continuous source of public health professionals who can deliver frontline services at the federal, state, tribal, local, and territorial levels. The article describes preliminary evaluation findings for PHAP. Design: The evaluation's primary purposes are to assess the quality and effectiveness of PHAP, determine its value and impact, and provide information to continuously improve the program. Because the evaluation is both formative and summative and focuses on aggregate outputs and outcomes of PHAP, the methodology is complex and builds over time as different cohorts cycle into and out of the program. Results presented are outcomes of various Web-based surveys and reporting systems. Participants: Four PHAP cohorts, consisting of 579 individuals, participated in 1 or more of the evaluation activities described in this article. Results: The majority of participants report satisfaction with their PHAP experiences, and 74% of recent graduates indicate they are continuing their careers or education in public health immediately after program completion. Seventy-eight percent of recent PHAP graduates who accept a job in public health are employed by the federal government. One year post-PHAP, 74% of alumni report that PHAP has been influential in their careers. Conclusion: CDC's investment in PHAP has increased the capacity and capabilities of the public health workforce. Results presented are early indicators of program quality, effectiveness, and impact. Today's public health workers are asked to do more with less, in the face of a dynamic array of complex public health challenges. PHAP offers public health agencies assistance in tackling these losses and challenges.